Study of transfer free graphene formation - Roy, Sajib; Galib, O.F.M Abdul (BRAC University, 2013)
The method of using CVD or Chemical Vapor Deposition [1-2] in the formation of graphene synthesis has recently progress quite a lot. The material shows exceptional electronic properties and also characterizes suspended graphene resonators. But the fabrication of this material involves the transfer of graphene from its copper catalyst to the required substrate using wet chemical etching method. This transfer procedure introduces metal residues, wrinkles and holes in the graphene. These issues are necessary to be dealt with and hence provide the need for a transfer-free fabrication method for suspended graphene, using CVD method. In this paper we fabricate suspended graphene without the use for any transfer technique. It can be grown both using a catalyst like thin copper films, and non-catalyst like directly on a dielectric substrate. Such a fabrication procedure includes the growth of graphene by CVD followed by the deposition of Au/Ti electrodes defined by e-beam lithography (ebl). Later on there will be graphene etching using oxygen plasma. The structures in the end are made suspended by chemically etching the substrate layer at the top and later on dried.